2012
DOI: 10.1002/jsfa.5617
|View full text |Cite
|
Sign up to set email alerts
|

The influence of organic and conventional cultivation systems on the nutritional value and content of bioactive compounds in selected tomato types

Abstract: The organic growing system affects tomato quality parameters such as nutritional value and phenolic compound content. The second significant factor of nutritional value of tomato is the type of fruits. It would be necessary to continue this study as a long-term experiment in order to eliminate the influence of seasonality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
106
1
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(121 citation statements)
references
References 16 publications
11
106
1
3
Order By: Relevance
“…Magkos et al (2001) reviewed that organically grown leafy vegetables and potatoes have higher levels of vitamin C. In addition, higher phytochemical content and total antioxidant activity was observed in organic oranges (Tarozzi et al, 2006) and higher levels of phenolic compounds were found in organic apples (Petkovsek et al, 2010) compared to the counterparts produced in integrated systems. In a comparative study carried out with two types of tomato (standard and cherry), Hallmann (2012) also found that organic fruits contained higher contents of total sugars, vitamin C and total flavonoids. In turn, Cwalina-Ambroziak and Amarowicz (2012) stated that the use of biological and fungicidal control agents was negatively correlated with the levels of carotenoids and phenolic compounds in tomato fruits.…”
Section: Introductionmentioning
confidence: 95%
“…Magkos et al (2001) reviewed that organically grown leafy vegetables and potatoes have higher levels of vitamin C. In addition, higher phytochemical content and total antioxidant activity was observed in organic oranges (Tarozzi et al, 2006) and higher levels of phenolic compounds were found in organic apples (Petkovsek et al, 2010) compared to the counterparts produced in integrated systems. In a comparative study carried out with two types of tomato (standard and cherry), Hallmann (2012) also found that organic fruits contained higher contents of total sugars, vitamin C and total flavonoids. In turn, Cwalina-Ambroziak and Amarowicz (2012) stated that the use of biological and fungicidal control agents was negatively correlated with the levels of carotenoids and phenolic compounds in tomato fruits.…”
Section: Introductionmentioning
confidence: 95%
“…The content of polyphenols (flavonoids and phenolic acids) in beetroot juices was determined by HPLC method, with identification of individual phenolic compounds according to the Fluca and Sigma Aldrich standards with a purity of 99.5% (Shimazu equipment, USA Manufacturing Inc, USA: two pump LC-20AD, controller CBM-20A, column oven SIL-20AC, spectrometer UV/Vis SPD-20 AV) (Hallmann, 2012). Weighted amounts of beetroot juice samples were put into the plastic test tubes, then 1 ml of methanol with 1% ascorbic acid were added, mixed thoroughly by vortex and incubated in an ultrasonic bath (20 min at 20 °C).…”
Section: Chemical Analysesmentioning
confidence: 99%
“…Lycopene values in field-grown tomatoes obtained by different investigators ranged from 36 to 119.4 mg·kg −1 [30]. In the study of Hallmann et al (2012) [31], the conventional farm received more nitrogen (N) than the organic farm. Conventional tomatoes had an appreciably higher content of lycopene compared to organic tomatoes.…”
Section: Lycopene Content In Cultivated Tomatoesmentioning
confidence: 99%
“…In recent years efforts are being made to understand relationships between crop management and antioxidant micro constituents of fruits and vegetables as these foods are the principal sources of flavonoids in the Western diet [4]. Lycopene, which comprises about 80%-90% of the total carotenoids of red ripe tomatoes is the most effective antioxidant among all carotenoids through its quenching activity of singlet oxygen and scavenging of peroxyl radicals [31,35,36]. Lycopene content is the most sought-after quality desired by the food industry and consumers [30].…”
Section: Lycopene Content In Cultivated Tomatoesmentioning
confidence: 99%